Pemikiran Tauhid dalam Tasawuf Sunni dan Falsafi - Aris Fachrizal, Muhammad; Arif, Ajie; Maryati, Rasah; Sagimin; Barmawan (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
This community service project aims to introduce and comparatively examine the concept of tawḥīd within two major schools of Sufism Sunni Sufism and Philosophical Sufism while highlighting their relevance to contemporary spiritual needs. Using a qualitative-descriptive and participatory approach, the activity was carried out at the Bonavida Foundation, Haurgelis, on May 6, 2025, involving foster children, local community members, and foundation volunteers. The results revealed a significant improvement in participants’ understanding of tawḥīd values, reflected in their ability to distinguish between the transcendence emphasized in Sunni Sufism and the immanence stressed in Philosophical Sufism. Interactive lectures and reflective discussions successfully nurtured deeper and more applicable spiritual awareness in daily life. Furthermore, the integration of orthodox and philosophical perspectives in Sufism proved to offer a balanced, rational, and contextually relevant spiritual foundation for modern society. Thus, this program served not only as a medium for disseminating religious knowledge but also as an effort to foster spiritual empowerment and strengthen tawḥīd-based Islamic character amidst contemporary challenges.